Accuracy of Bit Error Probability for W-CDMA System Using Code Tree - Ibrahim, A. H. (Engineering, Technology & Applied Science Research, 2018)
W-CDMA is radio access utilized for 3G cell frameworks. A code tree allocation scheme is one of the most explored channelization techniques, used to improve system performance and capacity through adjustable data rates. This work investigates the accuracy of bit error probability for W-CDMA system using code tree orthogonal variable spreading factor (OVSF) codes, compared to pseudo-noise (PN) codes under various noise conditions, such as additive white Gaussian Noise (AWGN) and Random Noise (RN). Results are carried out theoretically and by computer simulation. The simulation includes the scenario of simple model representation for W-CDMA system. It was concluded that, the system has better performance using OVSF compared with PN code under different noisy channels.